Gene regulation in Giardia lambia involves a putative microRNA derived from a small nucleolar RNA. - Wei Li; Ashesh A Saraiya; Ching C Wang (Public Library of Science (PLoS), 2011)
Two core microRNA (miRNA) pathway proteins, Dicer and Argonaute, are found in Giardia lamblia, a deeply branching parasitic protozoan. There are, however, no apparent homologues of Drosha or Exportin5 in the genome. Here, we report a 26 nucleotide (nt) RNA derived from a 106 nt Box C/D snoRNA, GlsR2. This small RNA, designated miR5, localizes to the 3' end of GlsR2 and has a 75 nt hairpin precursor. GlsR2 is processed by the Dicer from Giardia (GlDcr) and generated miR5. Immunoprecipitation of the Argonaute from Giardia (GlAgo) brought down miR5. When a Renilla Luciferase transcript with a 26 nt miR5 antisense sequence at the 3'-untranslated region (3' UTR) was introduced into Giardia trophozoites, Luciferase expression was reduced ∼25% when synthetic miR5 was also introduced. The Luciferase mRNA level remained, however, unchanged, suggesting translation repression by miR5. This inhibition was fully reversed by introducing also a 2'-O-methylated antisense inhibitor of miR5, suggesting that miR5 acts by interacting specifically with the antisense sequence in the mRNA. A partial antisense knock down of GlDcr or GlAgo in Giardia indicated that the former is needed for miR5 biogenesis whereas the latter is required for miR5-mediated translational repression. Potential targets for miR5 with canonical seed sequences were predicted bioinformatically near the stop codon of Giardia mRNAs. Four out of the 21 most likely targets were tested in the Luciferase reporter assay. miR5 was found to inhibit Luciferase expression (∼20%) of transcripts carrying these potential target sites, indicating that snoRNA-derived miRNA can regulate the expression of multiple genes in Giardia.